A one-pot synthesis of omarigliptin and its analogues through stabilized beta-amino ketone intermediate. Issue 4 (16th February 2017) - Li, You; Liu, Tongchao; Li, Chungang; Xiong, Bing; Zhao, Dongmei; Cheng, Maosheng; Chen, Guohua; Shen, Jingkang; Chen, Yue-Lei
ABSTRACT: We have discovered a unique stabilization condition for beta -amino ketone7 . With compound7 as an unprecedented intermediate, omarigliptin1 could be prepared in a highly efficient one-pot procedure with good yield. Also with this intermediate7, some analogues of omarigliptin1 were readily prepared for the first time. GRAPHICAL ABSTRACT: